Current Situation and Solutions of Laboratory Safety Management in Medical Colleges and Universities - Li, Ruirui (Journal of Theory and Practice of Social Science, 2023)
There are teaching laboratories and research laboratories in the laboratory, and their safety guarantee is related to the overall development of the school. Therefore, analyzing the current situation of laboratory safety work in medical colleges and universities, grasping the safety hazards such as incomplete safety management systems, daily supervision, and non-standard waste disposal in medical college laboratories, and proposing corresponding countermeasures and suggestions, can promote the scientific, standardized, and standardized safety management of medical college laboratories, and improve and improve the level of laboratory safety management.